The Immunomodulatory Effect of Triptolide on Mesenchymal Stromal Cells - He, Haiping; Takahashi, Atsuko; Mukai, Takeo; Hori, Akiko; Narita, Miwako; Tojo, Arinobu; Yang, Tonghua; Nagamura-Inoue, Tokiko (Frontiers in Immunology, 2021)
Mesenchymal stromal cells (MSCs) are known to have immunosuppressive ability and have been used in clinical treatment of acute graft-versus-host disease, one of severe complications of the hematopoietic stem cells transplantation. However, MSCs are activated to suppress the immune system only after encountering an inflammatory stimulation. Thus, it will be ideal if MSCs are primed to be activated and ready to suppress the immune reaction before being administered. Triptolide (TPL) is a diterpene triepoxide purified from a Chinese herb, Tripterygium wilfordii Hook.f., and has been shown to possess anti-inflammatory and immunosuppressive properties in vitro. In this study, we aimed to use TPL to prime umbilical cord-derived MSCs (TPL-primed UC-MSCs) to enter a stronger immunosuppressive status. UC-MSCs were primed with TPL, which was washed out thoroughly, and the TPL-primed UC-MSCs were resuspended in fresh medium. Although TPL inhibited the proliferation of UC-MSCs, 0.01 μM TPL for 24 hours was tolerable. The surface markers of TPL-primed UC-MSCs was identical to that of non-primed UC-MSCs. TPL-primed UC-MSCs exhibited stronger anti-proliferative effect for activated CD4+ and CD8+ T cells in the allogeneic mixed lymphocyte reaction assay than the non-primed UC-MSCs. TPL-primed UC-MSCs promoted the expression of IDO-1 in the presence of IFN-γ, but TPL alone was not sufficient. Furthermore, TPL-primed UC-MSCs showed increased expression of PD-L1. Conclusively, up-regulation of IDO-1 in the presence of IFN-γ and induction of PD-L1 enhances the immunosuppressive potency of TPL-primed UC-MSCs on the proliferation of activated T cells. Thus, TPL- primed MSCs may provide a novel immunosuppressive cell therapy.